Comprehensive study of the lipid from whelk (Chlorostoma rusticum and Neverita didyma) with emphasis on characterization of phospholipid molecular species by shot-gun strategy - Zhong-Yuan Liu; Kai-Qi Gang; Fa-Wen Yin; Hong-Kai Xie; Liang Song; Da-Yong Zhou (Journal of Food Bioactives, 2019)
In the present study, an effective shot-gun lipidomic methodology was established to determine the glycerophospholipid (GP) molecular species of two species of edible marine whelks (Chlorostoma rusticum and Neverita didyma). Simultaneously, the lipid content, lipid classes, phospholipid (PL) subclasses and fatty acid compositions were also investigated. Over 210 molecular species of GP including glycerophosphocholine, lysoglycerophosphocholine, glycerophosphoethanolamine, lysoglycerophosphoethanolamine, glycerophosphoserine, lysoglycerophosphoserine, glycerophosphoinositol and lysoglycerophosphoinositol were characterized in the two abovementioned whelk species. The predominant GP molecular species contained n-3 long chain polyunsaturated fatty acid (n-3 LC-PUFA), especially docosahexaenoic acid and eicosapentaenoic acid. Meanwhile, PL (57.70-58.86% of total lipids) and PUFA (21.69-37.68% of total FA) take large proportions in whelk lipids. Among PL, phosphatidylcholine (50.58-52.41 mol%) and phosphatidylethanolamine (27.67-32.73 mol%) were dominant. Therefore, marine whelks turn out to be promising source of n-3 LC-PUFA existed in PL form and thus directly contribute to the health benefits of consumer.